Stabilization of a brushed DC motor with the port controlled Hamiltonian approach - Morillo Piña, Atilio; Rios, E. Miguel; Acosta, Vivian (Rev. Téc. Fac. Ing. Univ. Zulia)
The main objective of this paper is to present an application of the port controlled Hamiltonian approach to achieve stabilization of electromechanical system. For this purpose we have selected the model of a DC brushed motor, which have been shown to be useful in illustrating some nonlinear control techniques. By means of the application of conversion of energy principles, the brushed DC motor is modeled in a suitable form, allowing instrumentally to dispose of the total energy function of the system, which carries on the mechanical and electrical effects. On the ground of the total energy function, it is possible to express the system In the port controlled Hamiltonian form, which clearly describes the interconnection and damping structures of the system, and the input and output ports of energy. Once we have reached this representation, the result is the passivation of the system hence by means of the application of the interconnection and damping assignment passivity based control methods, we obtain the synthesis of a static feedback stabilizing control.